Greywater Flow Characteristics for Closed Channel Maintenance - Ratna Bachrun; . Santi; Surya Baskara (Salehan Institute of Higher Education, 2023)
Knowing the characteristics of wastewater and its interaction with the channel is crucial to finding a suitable model and maintenance method to solve the closed channel problem. The purpose of this study is to find the relationship and how much it influences the characteristics of wastewater in closed channels and analyze the limit deposit velocity (LDV) of wastewater so that there is no deposition. The parameters used to analyze wastewater characteristics are density, oil and fat, specific gravity, total suspended solids, total dissolved solids, and kinematic viscosity. The parameters used to analyze the flow characteristics in closed channels are velocity, discharge, Reynolds number, friction coefficient, energy loss, and hydraulic gradient. The method used is experimental research by simulating a closed-channel model prototype. The closed channel model is made from an acrylic pipe with a length of 6 m and a pipe diameter of 0.064 m. Simulations on each wastewater sample and the discharge variations used were 0.005, 0.004, 0.003, and 0.0015 m3/s. Velocity measurements at a 0.5 pipe water level height and distances of 0, 2, 4, and 6 m. The results showed that the nature and composition of the wastewater the flow velocity. The large value of wastewater parameters shows that the flow velocity is small. The wastewater content is considered a load that must be transported to the end of the closed channel. When the discharge increases, the velocity will increase, Reynolds number will increase, and the energy loss will be large, while the friction coefficient is inversely proportional to Reynolds number. The velocities of clean water samples are 2.90 - 1.07 m/s, tofu - making is 2.83 - 1.07 m/s, household is 2.74 - 0.85 m/s, laundry is 2.84 - 1.03 m/s, and the workshop is 2.54 - 0.66 m/s. The limit deposit velocity (LDV) for household wastewater is 1.49 m/s to prevent deposition in closed channels. Doi: 10.28991/CEJ-2023-09-01-03 Full Text: PDF